2011
DOI: 10.1111/j.1365-2141.2011.08671.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducing apoptosis in chemotherapy‐resistant B‐lineage acute lymphoblastic leukaemia cells by targeting HSPA5, a master regulator of the anti‐apoptotic unfolded protein response signalling network

Abstract: SummaryWe present previously unknown evidence that the immunoglobulin heavy chain binding protein BIP/HSPA5, also known as glucose regulated protein (GRP)78, serving as a pivotal component of the pro-survival axis of the unfolded protein response (UPR) signalling network, is abundantly expressed in relapsed B-lineage acute lymphoblastic leukaemia (ALL) and contributes to chemotherapy resistance of leukaemic B-cell precursors. The resistance of B-lineage ALL cells to the standard anti-leukaemic drug vincristine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 54 publications
(151 reference statements)
8
57
0
3
Order By: Relevance
“…In agreement with PI3K/AKT as an effector for cytosine arabinoside (AraC) resistance in leukemia, 18 we observed that manipulation of GRP78 expression level alters the sensitivity of human leukemic cells to AraC-induced apoptosis. These, coupled with the emerging association of elevated GRP78 expression in leukemic blasts of adult patients and early relapse in childhood leukemia reported here and by others, [19][20][21] suggest that GRP78 is a novel therapeutic target for leukemia. An Inside Blood analysis of this article appears at the front of this issue.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…In agreement with PI3K/AKT as an effector for cytosine arabinoside (AraC) resistance in leukemia, 18 we observed that manipulation of GRP78 expression level alters the sensitivity of human leukemic cells to AraC-induced apoptosis. These, coupled with the emerging association of elevated GRP78 expression in leukemic blasts of adult patients and early relapse in childhood leukemia reported here and by others, [19][20][21] suggest that GRP78 is a novel therapeutic target for leukemia. An Inside Blood analysis of this article appears at the front of this issue.…”
supporting
confidence: 68%
“…Recently, it is reported that resistance of B-ALL cells to the anti-leukemic drug vincristine was suppressed by (Ϫ)-epigallocatechin gallate, which inhibits the antiapoptotic function of GRP78 by targeting to its ATP-binding domain. 21,45 Furthermore, chemoresistant B-ALL cells underwent apoptosis when exposed to a doxorubicin-conjugated penetrating cyclic anti-GRP78 peptide targeting cell surface GRP78. 21 Although the role of GRP78 in human leukemia and recurrence remains to be determined, emerging evidence suggests elevated Grp78 expression in patient leukemic blasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of GRP78 in the hematopoietic system is just emerging, however, recent study clearly revealed involvement of GRP78 in hematopoietic stem cell survival and lymphogenesis (Wey et al 2012a). In addition, it has been shown that GRP78 expression is up-regulated in various forms of human leukaemia and implicated as causative factor for therapeutic resistance and early relapse (Tanimura et al 2009;Rosati et al 2010;Uckun et al 2011;Wey et al 2012b). In our experiments, we have detected GRP78 to be expressed in non-treated HL-60 cells and treatment of the cells with NaBu for 48 hours was associated with decrease of GRP78 level.…”
Section: Discussionsupporting
confidence: 53%
“…For example, the immunoglobulin heavy chain binding protein, BIP/HSPA5, a pivotal component of the prosurvival axis of the unfolded protein response signaling network, is abundantly expressed in relapsed B-cell ALL and has been proposed as a chemotherapy-resistance biomarker. 40 A murine model also detailed that obesity might be a factor in resistance, with ALL cells preferentially migrating to a proposed protective microenvironment within adipose cells. 41 A number of Phase I and II clinical trials of novel agents are currently underway to investigate novel targeted therapies for relapsed ALL to improve outcomes.…”
Section: Treatment Of Relapsed Philadelphia-negative Allmentioning
confidence: 99%